Circular RNAs (circRNAs) in Health and Disease - Shahnaz Haque (Genes, 2017)
Splicing events do not always produce a linear transcript. Circular RNAs (circRNAs) are a class of RNA that are emerging as key new members of the gene regulatory milieu, which are produced by back-splicing events within genes. In circRNA formation, rather than being spliced in a linear fashion, exons can be circularised by use of the 3′ acceptor splice site of an upstream exon, leading to the formation of a circular RNA species. circRNAs have been demonstrated across species and have the potential to present genetic information in new orientations distinct from their parent transcript. The importance of these RNA players in gene regulation and normal cellular homeostasis is now beginning to be recognised. They have several potential modes of action, from serving as sponges for micro RNAs and RNA binding proteins, to acting as transcriptional regulators. In accordance with an important role in the normal biology of the cell, perturbations of circRNA expression are now being reported in association with disease. Furthermore, the inherent stability of circRNAs conferred by their circular structure and exonuclease resistance, and their expression in blood and other peripheral tissues in association with endosomes and microvesicles, renders them excellent candidates as disease biomarkers. In this review, we explore the state of knowledge on this exciting class of transcripts in regulating gene expression and discuss their emerging role in health and disease.